Issues, Strategies and Challenges: The Dimensions of Rural Development in Indian Geography - SINGH, Dr. MAUKAM (The journal of contemporary issues in business and government, 2019)
More and more nations have been aware of the powerful method to assist them to improve their economy, namely to manage the rural environment. The rural sector is essential to society since it produces civilisation progress and development, so that human aspirations for better life are maintained and met. Rural and economic growth are linked since the majority of development resources are from rural communities. The paper's main purpose is to evaluate rural economic circumstances and examine the villages' problems and difficulties. The report aims at framing a strategy framework for rural economic development that would help India to build a brighter future.